'We practise every day': parents' attitudes towards early science learning and education among a sample of urban families in Ireland. Issue 6 (1st November 2020) - Gilligan, Therese; Lovett, Judy; McLoughlin, Eilish; Murphy, Clíona; Finlayson, Odilla; Corriveau, Kathleen; McNally, Sinéad
ABSTRACT: Educational policies increasingly emphasise early childhood science engagement. As key influencers in children's early learning, parents (n = 85) attending a science workshop in three urban schools in Ireland were surveyed regarding their attitudes towards science. Seventy per cent of parents believed that science education should begin in the pre-school years, before the age of four. Despite high levels of education, at least half of the parents expressed some lack of confidence in talking about, and in doing science with, their young children. Parents who reported less confidence in doing science activities with their children also reported reduced frequency of activities for five out of the seven science learning opportunities listed. Mothers, compared to fathers, reported less confidence in doing science activities with their children. Findings indicate that parents' confidence in science may impact early science experiences and highlight parents as a key support for increasing early science engagement.